LEGAL REGIME FOR SAFETY OF FLIGHTS OF CIVIL AIRCRAFT IN THE SITUATION OF ARMED CONFLICT ON THE TERRITORY OF THE STATE - Волостних, Володимир Сергійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article, based on the legal assessment of documents developed within the framework of ICAO, defines the legal regime for ensuring the safety of flights of civil aircraft in the situation of armed conflict in the territory of the state. Methods: analysis of documents, generalization of the results. Results: measures to be taken by states in situations that pose potential hazards for civilian aircraft operations have been identified. Discussion: the problems of national legislation and the implementation of the norms of foreign legislation in the norms of domestic legislation.